2024
DOI: 10.1101/2024.01.30.577933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence, Structure and Functional space ofDrosophila de novoproteins

Lasse Middendorf,
Bharat Ravi Iyengar,
Lars A. Eicholt

Abstract: During de novo emergence, new protein coding genes emerge from previously non-genic sequences. The de novo proteins they encode are dissimilar in composition and predicted biochemical properties to conserved proteins. However, many functional de novo proteins indeed exist. Both identification of functional de novo proteins and their structural characterisation are experimentally laborious. To identify functional and structured de novo proteins in silico, we applied recently developed machine learning based too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 161 publications
(246 reference statements)
0
1
0
Order By: Relevance
“…MD (molecular dynamics) simulation studies have revealed that most de novo proteins are flexible in structure and a minority of them adopt well-known protein structures ( Middendorf and Eicholt 2024 ; Peng and Zhao 2024 ). Despite the tendency of de novo proteins to be disordered with few (or no) orthologs, AlphaFold2's predictions reveal that they generally achieve higher-confidence scores per residue (predicted local distance difference test [pLDDT]) than random sequences ( Middendorf et al 2024 ). The AlphaFold2 performs the MD refinement (called “relax” in AlphaFold2 terminology) using OpenMM ( Jumper et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…MD (molecular dynamics) simulation studies have revealed that most de novo proteins are flexible in structure and a minority of them adopt well-known protein structures ( Middendorf and Eicholt 2024 ; Peng and Zhao 2024 ). Despite the tendency of de novo proteins to be disordered with few (or no) orthologs, AlphaFold2's predictions reveal that they generally achieve higher-confidence scores per residue (predicted local distance difference test [pLDDT]) than random sequences ( Middendorf et al 2024 ). The AlphaFold2 performs the MD refinement (called “relax” in AlphaFold2 terminology) using OpenMM ( Jumper et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%